2020
DOI: 10.1186/s12877-020-01718-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of probable sarcopenia in community-dwelling older Swiss people – a cross-sectional study

Abstract: Background: The European Working Group on Sarcopenia in Older People has recently defined new criteria for identifying "(probable) sarcopenia" (EWGSOP2). However, the prevalence of probable sarcopenia, defined by these guidelines, has not been determined extensively, especially in the oldest old. This study aims to determine the prevalence of probable sarcopenia in older, community-living people and its association with strength-related determinants. Methods: Handgrip strength and reported determinants (age, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
41
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 42 publications
(71 reference statements)
6
41
1
2
Order By: Relevance
“…This is broadly in agreement with previous studies of probable sarcopenia based on EWGSOP2 guidelines. Some authors, in assessing muscle weakness for probable sarcopenia, used hand grip strength, 9 , 10 while others also included performance on chair rise test. 7 , 8 Wearing et al reported a prevalence of 26.3% and 28.0% for probable sarcopenia in females and males, respectively (n = 219), although this study was conducted in a study population of advanced age (84.1 ± 5.7 years).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is broadly in agreement with previous studies of probable sarcopenia based on EWGSOP2 guidelines. Some authors, in assessing muscle weakness for probable sarcopenia, used hand grip strength, 9 , 10 while others also included performance on chair rise test. 7 , 8 Wearing et al reported a prevalence of 26.3% and 28.0% for probable sarcopenia in females and males, respectively (n = 219), although this study was conducted in a study population of advanced age (84.1 ± 5.7 years).…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 Wearing et al reported a prevalence of 26.3% and 28.0% for probable sarcopenia in females and males, respectively (n = 219), although this study was conducted in a study population of advanced age (84.1 ± 5.7 years). 10 In an analysis of the Korean Frailty and Ageing Cohort Study (n= 2099, mean age 75.9 ± 4.0 years), 8 24% of participants had probable sarcopenia. While Dodds et al estimated a prevalence of 19% amongst the 1946 British birth cohort aged 69 years (n = 1686).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is classified as a disease under the World Health Organization (WHO)'s International Statistical Classification of Diseases and Related Health Problems (ICD) (3). The prevalence of sarcopenia ranges between 9 and 51%, and probable or possible sarcopenia between 26.3 and 73.3% depending on the case finding approach, population subgroup, and definitions used (4)(5)(6)(7)(8). Aging is a known risk factor for sarcopenia and the number of individuals with sarcopenia is projected to increase by 72.4% in Europe between 2016 and 2045 (9,10).…”
Section: Introductionmentioning
confidence: 99%